The rate of hepatic glycogen and its relationship to glycemic - Urteaga Ballón, Oscar (1943)
The author performed serially liver biopsies in adult dogs, using local anesthesia. He used Best´s Carmin for detecting glycogen. In some animals, he investigated the glycemia before each biopsy. He also studied the effect of several substances upon the glycogen content of the liver.